Repurchase Intention: Examined Through Website Design, Digital Technology, and Service Quality of SOP Official Medan - Liandy, Nicholas; Sri Rezeki; Nizam Azmal Abdul Malek; Dr Asliza Yusof (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
SOP Official Medan, a retail unit selling health supplements since 2019, connects producers to consumers through digital platforms and quality service. This study examines consumer repurchase intention based on website design, digital technology, and service quality, using a quantitative approach. A sample of 180 respondents was selected through purposive sampling, with data collected via a Likert scale questionnaire and analyzed using multiple linear regression in SPSS. The results reveal that website design, digital technology, and service quality positively and significantly influence repurchase intention. An attractive, user-friendly website enhances customer satisfaction and encourages repeat purchases. Innovative digital technology streamlines transactions, boosting convenience and reinforcing repurchase intentions. Notably, responsive and proactive service quality has the greatest impact on repurchase intention. These findings underscore the importance of integrating website design, digital technology, and quality service to create an optimal shopping experience and foster customer repurchase intention at SOP Official Medan.